The effect of curing light distance on the effectiveness of cure of bulk-fill resin-based composites / Rana Abdelbaset Lotfy Diab - Rana Abdelbaset , Lotfy Diab (2019)
Objectives: To investigate the effect of different curing light distances on the surface hardness (SH) and the effectiveness of cure of bulk-fill resin-based composites (RBCs). Methodology: Two bulk-fill RBCs (Tetric N Ceram® Bulk Fill [TN] and Filtek™ Bulk Fill [FK]) were evaluated. Cylindrical RBC specimens of 5 mm diameter and 4 mm height were fabricated using black Perspex® acrylic moulds. Photopolymerization of the RBC specimens was carried out at different light-curing distances (0 mm, 2 mm, 4 mm, 6 mm and 8 mm) and stored for 24 hours at 37°C in 100% relative humidity. The SH (n=12) of the top and bottom surfaces of each specimen was assessed using a Knoop hardness micro-indentation tester. The bottom to top SH values were calculated to obtain the hardness ratio (HR) for each specimen. HR of the two bulk-fill RBCs were compared. Results: Data were analysed using one-way ANOVA and Tukey’s post hoc test (α<0.05). At various curing light distances, the mean SH for TN ranged between 34.45 and 41.24 for the top surface and between 9.12 and 17.56 for the bottom surface. However, for FK, the mean SH ranged from 44.76 to 51.12 and from 32.57 to 37.60 for the top and bottom surfaces respectively. The mean HR values which characterizes the effectiveness of cure ranged from 0.27 to 0.46 for TN and from 0.68 to 0.79 for FK at different curing light distances. The HR of TN at 8 mm curing light distance was significantly lower in comparison to the other curing light distances. However, for FK, 8 mm curing light distance was only significantly lower than that of 0 mm. FK had significantly higher HR than TN at different curing light distances. Conclusions: The top and bottom SH of TN and FK are affected by the curing light distance. The HR of TN and FK resulted in a linear relationship with the curing light distance. The effectiveness of cure decreased with the increase of the curing light iv distance. The effectiveness of cure of bulk-fill resin-based composites is materialdependent. Keywords: Bulk-fill, Resin-based composites, curing light distance, Surface hardness effectiveness of cure.